The effect of Aβ seeding is dependent on the presence of knock-in genes in the AppNL−G−F mice - Lacoursiere, Sean G.; Safar, Jiri; Westaway, David; Mohajerani, Majid H.; Sutherland, Robert J. (Frontiers in Dementia, 2022)
Alzheimer's disease (AD) is characterized by the prion-like propagation of amyloid-β (Aβ). However, the role of Aβ in cognitive impairment is still unclear. To determine the causal role of Aβ in AD, we intracerebrally seeded the entorhinal cortex of a 2-month-old AppNL−G−F mouse model with an Aβ peptide derived from patients who died from rapidly progressing AD. When the mice were 3 months of age or 1 month following seeding, spatial learning and memory were tested using the Morris water task. Immunohistochemical labeling showed seeding with the Aβ was found accelerate Aβ plaque deposition and microgliosis in the AppNL−G−F mice, but this was dependent on the presence of the knocked-in genes. However, we found no correlation between pathology and spatial performance. The results of the present study show the seeding effects in the AppNL−G−F knock-in model, and how these are dependent on the presence of a humanized App gene. But these pathological changes were not initially causal in memory impairment.